Mineral nutrition of rubber tree III: nutrients cycling in a rubber tree plantation at Rio Branco, AC, Brazil - Haag, H.P.; Guerrini, I.A. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1984)
Leaves, systems and branches from trees of one year up to four years were collected from a plantation located at the BONAL S/A in Rio Branco, AC, Brazil the soilunder the plantation is classified as Red-yellow Latossol. Samples of the leguminous (Pueraria phaseoloides) and liter were also collected in order to estimate the total amounts of nutrients extracted and the cycling of the nutrients in the system. The results obtained showed that: - The dry matter produced (3,185 kg/ha) by the leguminous at 48 months is much greater than that produced by the rubber trees (2,787 kg/ha) at the same age. - The dry matter produced by the liter (5,912 kg/ /ha) is also greater than that produced by the rubber trees . - The total amount of nutrients content in the leguminous at 48 .months is estimate in 164 kg/ha in the rubber trees is approximate in 57 kg/ha. - The total amount of nutrients content in the mulch covering the soil at 48 months is estimate in 196 kg/ha. From the total amounts of nutrients extracted from the soil by the rubber trees and the leguminous at 48 months the following porcentage in nutrients return to the soil: K-21.7%; P-37.3%; S-51.2%; Zn-51.8%; Mg-54.4%; B-54.7%; Ca-56.4%; Cu-57-5%; N-58.5%; Mn-74.5% and Fe--90.7%.